Trauma Resuscitation Time at A Tertiary Care Hospital in Oman: A Retrospective Observational Study - Maysa Al-Maawali; Salim Al Rawahi; Hani Al-Qadhi (Open Journal of Trauma - Peertechz Publications, 2020)
Introduction: Trauma is an important worldwide public-health problem. This study aims to evaluate the median trauma resuscitation time (TRT) at Sultan Qaboos University Hospital (SQUH), Oman, and to investigate the reasons for delay in trauma resuscitation. Documenting TRT can be utilized to assess areas of improvement for trauma team performance, ensuring a high-quality resuscitation management that improves trauma patients' survivability.   Methods:  This is a retrospective observational study. It included all trauma patients attended the Emergency Department (ED) and required trauma team resuscitation in the period between June 2016 and June 2017. Electronic Health Records (EHR) were accessed to retrieve data of 295 patients included. The TRT was obtained by calculating the difference between the time of the patient's arrival to the trauma bay and the time of the patient's disposition. Patients' demographics and clinical data such as GCS, trauma mechanism, trauma type, resuscitation procedures and outcomes were evaluated.  Results: A total of 270 patients were included in the final results; 25 patients were excluded for missing data. The median TRT was found to be 25 minutes (IQR= 17); the mean age was 26.9 ± 13.9 years; 85.6% patients were male; the mechanisms of injury were: motor vehicle collision (MVC) (45.9%), pedestrian struck (25.2%), fall (17.4%), stab injury (5.9%), crush injury (4.4%), burn (0.7%) and assault (0.4%); 67 (52.3%) patients required intubation, 19 (14.8%) patients required chest tube insertion, 2 (1.5%) patients required a central line was insertion, 13 (4.8%) patients required focused assessment with sonography in trauma (FAST) and 27 (10%) patients required cast application for upper and lower extremity fractures; 202 (74.8%) patients were admitted directly from the emergency department, 14 (5.2%) patients required emergent surgery, 34 (12.5%) patients were discharged home, 4 (1.5%) patients were referred to a different hospital and 16 (5.9%) patients died. Of those who died, 14 patients died during the resuscitation. Conclusion: We concluded from this study that patients with stab injury required more resuscitation time and the delay in resuscitation was observed among those who required FAST examination and intubation. Advanced Trauma Life Support training (ATLS), simulation-based training, and video review have all improved patient outcome and trauma team performance. Further prospective studies are warranted to address the limitations.